Termination of Prosecution Based on Restorative Justice At the Kapuas District Attorney's Office - Citranu, Citranu (PT. Hafasy Dwi Nawasena, 2024)
: The purpose of this study is to determine the procedure for termination of prosecution through the application of restorative justice at the Kapuas District Attorney's Office and to assess whether the rights and legal interests of victims have been fulfilled in the process. This research uses empirical legal research method by collecting primary data, and secondary data. The results of this study show that the application of restorative justice at the Kapuas State Attorney's Office is in accordance with what is stipulatedin the Attorney General's Regulation Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice. The process of terminating prosecution through restorative justice goes through several stages of verification and tiered assessment, starting from the analysis of requirements by the Kapuas District Attorney's Office, further verification by the Central Kalimantan High Prosecutor's Office, to the final decision approved by the Attorney General's Office through the Deputy Attorney General for General Crimes. The fulfilment of the victim's legal rights and interests in the application of restorative justice depends entirely on the victim's consent to the actions taken by the perpetrator. This is important because the fulfilment of the victim's rights is the main condition for achieving peace. If the rights of the victim have been fulfilled, a peace agreement will automatically be born, so that the process of termination of prosecution through restorative justice can be implemented effectively.